New Phraseological Units in the Armenian Sources of XVI-XVIII Centuries - POGHOSYAN, NORAYR (Bulletin of Yerevan University B: Philology, 2021)
Throughout a long period of time Armenology has extensively covered phraseological units in numerous works and dictionaries. However, further studies of original works, particularly those of the Late Middle Ages, reveal many more new phraseological units. Various works dating back to the period between 16th and 18th centuries have been studied. As a result of a thorough analysis, a number of new idioms and phraseological expressions were brought to light. Most of these idioms are not in use in Modern Armenian; while those that are considered active normally appear in modified forms. This article lists 150 new idioms, 100 of which were not included in dictionaries of idioms. They are considered to be genuine idioms of Early Modern Armenian.